Pan‐European survey on medication adherence management by healthcare professionals - Kamusheva, Maria; Aarnio, Emma; Qvarnström, Miriam; Hafez, Gaye; Mucherino, Sara; Potočnjak, Ines; Trečiokiene, Indre; Mihajlović, Jovan; Ekenberg, Marie; Boven, Job F. M.; Leiva‐Fernandez, Francisca (British journal of clinical pharmacology, 2024)
Aims While medication adherence (MA) is a key prerequisite for achieving optimal clinical and economic outcomes, nonadherence is highly prevalent. Assessing how healthcare professionals (HCPs) in Europe manage MA, focusing on measurement, reporting and interventions, is the subject of this study. Methods A cross‐sectional study was conducted among 40 European countries and quantitative analysis was conducted via an online survey. The multi‐language online survey was created using Webropol 3.0 survey and reporting tool. Descriptive statistics and chi‐squared tests were applied. Results In total, 2875 HCPs (pharmacists: 39.9%; physicians: 36.7%; nurses: 16.4%) from 37 European countries participated. The most used methods for MA assessment were direct communication with patients (86.4%) and referring to personal patient records (56.7%) (P < 0.0001). Physicians (74.9%) and nurses (58.8%) were more aware of problems related to MA in contrast to pharmacists (48.6%) (P < 0.001). Almost all HCPs (92.6%) indicated that MA‐enhancing interventions involved mainly direct communication with nonadherent patients (93.3%) and their caregivers (55.7%). Medication review and related optimization of therapy were mainly performed in Western European countries (46.8%). Technological solutions were ranked as one of the less applied approaches (10–15%) (P < 0.001). Conclusions HCPs in all European regions recognize MA management as an integral element of overall patient‐centred care. More efforts are needed to ensure timely, adequate and relevant MA assessment, reporting and improvement and involvement of all HCPs, especially among pharmacists who were generally less aware of MA issues. Promotion and use of digital technological solutions should be the focus of current and future clinical practice to optimize MA management processes.